Method of system design of the network of means of special control - Bezkorovayny, Volodymyr; Solonets, Oleksiy; Kulagin, Konstantin; Koshel, Tetyana; Petrov, Sergey; Koshel, Anatoliy (NTU "KhPI", 2017)
The subject matter of the article is the processes of system design of the network of special control means (NSCM). The aim is to develop an iterative scheme for the logical design of a network of special controls that will be based on the ideas of the aggregative-decomposition approach, system analysis and system design of complex systems. The objectives are: analysis of the features of the network of special control means as an object of design or reengineering; decomposition of the problem of optimization of NSCM to a multitude of tasks related to different hierarchical levels of decomposition, with their interrelationships on the initial data and the results of the solution; formulation of the requirements that the methods and procedures for solving the problems of optimization of the NSCM should satisfy; the development of an iterative logic scheme and the system design method for the NSCM. The methods used are: system analysis of design processes, cause-effect analysis, method of system design of complex systems. The following results are obtained. The analysis of the peculiarities of the network of special control means as an object of design or reengineering is carried out. Taking into account the characteristics of NSCM, decomposition of the problem of its optimization into a set of interrelated tasks related to different hierarchical levels of decomposition is performed. The scheme of the interrelationships of the selected tasks with the input data and the results of their solution is established. The requirements that must be met by methods and procedures for solving the problems of optimization of NSCM are defined. This allowed the development of an iterative logic scheme and on its basis the method of system design of NSCM. Conclusions. On the basis of the analysis of the interrelationships between the optimization problems of NSCM on the input data and the results of their solution, an iterative logic scheme and an interactive method of its system design are developed. It is expedient to use the obtained results for complex determination of the structure, topology, parameters and technology of functioning of NSCM. This will reduce the time to solve problems of designing, planning the development or reengineering of networks of funds, reduce the cost of their creation and operation, through joint solutions to improve the quality of solutions and, on this basis, improve their functional characteristics.

Предметом вивчення в статті є процеси системного проектування мережі засобів спеціального контролю (МЗСК). Мета – розробка ітераційної схеми логічного проектування мережі засобів спеціального контролю, що ґрунтуватиметься на ідеях агрегативно-декомпозиційного підходу, системного аналізу та системного проектування складних систем. Завдання: аналіз особливостей мережі засобів спеціального контролю як об'єкта проектування чи реінжинірингу; декомпозиція проблеми оптимізації МЗСК на множину задач, що відносяться до різних ієрархічних рівнів декомпозиції, з їх взаємозв'язками за вихідними даними та результатами розв'язання; формулювання вимог, яким повинні задовольняти ефективні методи та процедури розв'язання задач оптимізації МЗСК; розробка ітераційної логічної схеми та методу системного проектування МЗСК. Використовуваними методами є: системологічний аналіз процесів проектування, причинно-наслідковий аналіз, метод системного проектування складних систем. Отримані такі результати. Проведено аналіз особливостей мережі засобів спеціального контролю як об'єкта проектування чи реінжинірингу. З урахуванням особливостей МЗСК виконано декомпозицію проблеми її оптимізації на множину взаємопов'язаних задач, що відносяться до різних ієрархічних рівнів декомпозиції. Встановлено схему взаємозв'язків виділених задач за вхідними даними та результатами їх розв'язання. Визначено вимоги, яким повинні задовольняти ефективні методи та процедури розв'язання задач оптимізації МЗСК. Це дозволило розробити ітераційну логічну схему та на її основі метод системного проектування МЗСК. Висновки. На основі аналізу взаємозв'язків задач оптимізації МЗСК за вхідними даними та результатами їх розв'язання розроблено ітераційну логічну схему та інтерактивний метод її системного проектування. Отримані результати доцільно використовувати для комплексного визначення структури, топології, параметрів та технології функціонування МЗСК. Це дозволить скоротити час розв'язання задач проектування, планування розвитку чи реінжинірингу мереж засобів, скоротити витрати на їх створення й експлуатацію, за рахунок спільного розв'язання задач підвищити якість рішень і на цій основі покращувати їх функціональні характеристики.
Метод системного проектування мережі засобів спеціального контролю
Keywords: large-scale object; special control system; structure; topology; design; optimization; logical scheme of system design; великомасштабний об'єкт; система спеціального контролю; структура; топологія; проектування; оптимізація; логічна схема системного проектування